Empowering Secondary Students to Overcome Cyberbullying through Peer-Helper Training - Sadida, Nuri; Zakiah, Sari; Nursanti, Ade (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2020)
The number of cyberbullying cases in Indonesia is one of the highest in the world. Cyberbullying could impact the victims to have low academic motivation, depression, and suicidal thoughts. Most of the cyberbullying victims are high school students. Therefore, the training is designed to provide student knowledge about forms, characteristics, and the negative impacts of cyberbullying, so that students can overcome the impact. The training used a single-group pretest-posttest design, in which participants' knowledge and attitude were measured before and after training was delivered. The module contains two main topics: knowledge of cyberbullying, and how to make friends in a digital environment safely. As much as 60 students participated in the training. The result showed that there is an increasing score from pre-test to post-test (from 7.13 to 72). It can be concluded that the contents of the training could increase participants' knowledge regarding cyberbullying.